ANALISIS MOTIVASI BELAJAR SISWA KELAS XI PADA MATERI KOMPOSISI FUNGSI DAN INVERS TERHADAP APLIKASI WORDWALL - Pratiwi, Eka; Yani T, Ahmad; Siregar, Nurfadilah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The research used a descriptive qualitative approach to analyze the learning motivation of 38 students of class XI E SMA Santo Paulus Pontianak in learning function composition and inverse with the help of Wordwall application. Data were collected using a questionnaire containing ten indicator of learning motivation and interviews. The results showed that all indicators from the questionnaire were categorized good. The highest percentage of positive responses was on the responsibility indicator (90.13%) and on the desire to succeed indicator (86.94%). This finding is supported by interview data that shows Wordwall increases students' engagement, interest and perseverance and creates interesting and challenging learning. This study concludes that Wordwall application is effective in increasing students' learning motivation on the material of function composition and inverse.